2014
DOI: 10.1063/1.4866984
|View full text |Cite
|
Sign up to set email alerts
|

The accretion of solar material onto white dwarfs: No mixing with core material implies that the mass of the white dwarf is increasing

Abstract: Cataclysmic Variables (CVs) are close binary star systems with one component a white dwarf (WD) and the other a larger cooler star that fills its Roche Lobe. The cooler star is losing mass through the inner Lagrangian point of the binary and some unknown fraction of this material is accreted by the WD. One consequence of the WDs accreting material, is the possibility that they are growing in mass and will eventually reach the Chandrasekhar Limit. This evolution could result in a Supernova Ia (SN Ia) explosion … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 50 publications
1
28
0
Order By: Relevance
“…This contradicts standard theories for nova outbursts (Prialnik 1986;Prialnik & Kovetz 1995;Yaron et al 2005). WD masses can only grow in CVs if no mixing of core matter with accreted matter is assumed (Williams 2013;Starrfield 2015), which is unrealistic. However, given the large discrepancy between the observed and predicted WD mass distributions, we need to investigate all possible scenarios.…”
Section: Introductionmentioning
confidence: 50%
“…This contradicts standard theories for nova outbursts (Prialnik 1986;Prialnik & Kovetz 1995;Yaron et al 2005). WD masses can only grow in CVs if no mixing of core matter with accreted matter is assumed (Williams 2013;Starrfield 2015), which is unrealistic. However, given the large discrepancy between the observed and predicted WD mass distributions, we need to investigate all possible scenarios.…”
Section: Introductionmentioning
confidence: 50%
“…However, the main aspects of this picture have been contested by several authors. First, the existence of the stability strip has been questioned (e.g., Idan et al 2013;Starrfield 2014;Hillman et al 2015). In fact, no stable burning is reported in the Yaron et al (2005) tables either, although the ejected mass becomes zero at the highest mass-accretion rates.…”
Section: Discussionmentioning
confidence: 99%
“…Second, it has been suggested that mass accumulation at appreciable rates is possible in the broad range of the mass-accretion rates, including those traditionally considered to be associated with the nova regime. In fact, it has been claimed that any mass accumulation by the WD is associated with regular thermonuclear explosions (e.g., Starrfield 2014;Hillman et al 2015). In a related development, progenitor models have been proposed that involve WDs accreting in the presumably unstable nuclear burning regime throughout or at least a part of their accretion history (e.g., Starrfield et al 1985;Hachisu & Kato 2001;Hillman et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations